The intra-civil society relations and the role of the civil society groups in Philippine democratization from 1896-2001. - Go, Ruby jane M.
This study examines the relationship between and among civil society groups (CSGs) including religious institutions or traditional non-government organizations (TANGOs) and ideological forces in Iloilo city, as well as the role of the said civil society groups in relation to Philippine democratization from 1986 to 2001., The subjects of this study are religious institutions and ideological forces of the national and social democratic leaning, and the groups' respective key leaders. The leaders, who were visible from democratic transition to consolidation and only during consolidation, were interviewed. The conduct of this study was held from November 2003 to February 2004 in the city of Iloilo. This study found out that the relations between Iloilo-based CSGs after 1986 were affected by the ideological split at the national level of their organizations. In order to ease the conflict between the two forces, religious institutions intervened as mediator. All of the CSGs had their own strategies in uniting with each other for a common cause and made alliances and coalitions. The findings about the participation of the Catholic Church in Iloilo during democratic transition deviated from the mainstream analysis, which says that the Church was the major active proponent of anti-dictatorship actions.